Citrus aurantium ‘Changshan-huyou’—An ethnopharmacological and phytochemical review - Gao, Liang; Zhang, Hui; Yuan, Chun-Hui; Zeng, Ling-Hui; Xiang, Zheng; Song, Jian-Feng; Wang, Hua-Gang; Jiang, Jian-Ping (Frontiers in Pharmacology, 2022)
Citrus fruits are composed of oil cells layer, white membrane layer, pulp and seeds. The cultivar Citrus aurantium 'Changshan-huyou' (CACH) is a hybridization of Citrus grandis Osbeck and C. sinensis Osbeck. It is a rutaceae plant, and mainly grows in Changshan, Zhejiang, China. With the exploration of its high traditional values, it has been paid more and more attention by the scientific community in recent years. At present, one hundred and two chemical constituents have been identified from the pulp and peel of CACH, including volatile oils, terpenoids, phenols, limonins, sugars, etc. As the representative active component of CACH, phenols have been widely investigated. Studies have shown that CACH shows a variety of significant pharmacological activities, such as anti-inflammatory, antioxidant, hepatoprotective activity, respiratory system protection and intestinal regulation activity. This review mainly introduces the chemical constituents and pharmacological activities of CACH, and discusses its future research and development directions. It will provide theoretical basis for further research of its pharmacodynamic substances, functional mechanism and rational utilization.